The inner and outer of our thorax: silicone breast implants and pulmonary alveolar proteinosis. Issue 5 (3rd September 2015) - De Backer, H.; Darquennes, K.; Dooms, C.; Yserbyt, J.; Coolen, J.; Verschakelen, J.; Verbeken, E.; Vrints, I.; Wuyts, W.
Abstract : Pulmonary alveolar (phospholipo)proteinosis (PAP) is a rare lung disease, predominantly autoimmune in nature. This case report describes a patient with insidious dyspnoea since 5 ♣years and a milky appearance of her bronchoalveolar fluid, leading to the diagnosis of PAP. The onset of symptoms coincided with an exchange of her silicone breast implants. Giant cell reaction in axillary adenopathies pointed towards silicone leakage. Adjuvants, such as silicone, might boost pre-existing antigen reactions of the immune system, potentially leading to autoimmune phenomena.